ANALISIS PENYEBARAN HALLYU DI JEPANG - Enike, Iit Fitrix; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research analyzes the spread of Hallyu or what is generally known as the Korean Wave in Japan. Hallyu is a transnational phenomenon involving South Korean popular culture which is deliberately spread with certain purposes. Some of them are improving the quality of the economy and creating a good image for South Korea. There are various types of South Korean popular culture, namely music, films, dramas, clothing styles, and others. South Korean popular culture is spread to various countries in the world, one of which is Japan. These two countries have poor relations due to the colonialism carried out by Japan against South Korea. This also has an influence on the Japanese public's view of South Korea. The purpose of this research is to see the spread of Hallyu in Japan. The method used in this research is a qualitative method using several sources, namely journals, books, and websites. The spread of Hallyu in Japan can spread throughout the country, which can be proven by the holding of concerts by Korean singers in several cities or prefectures, the high ratings of national television broadcasts showing Korean dramas, and the many restaurants that specifically serve South Korean cuisine Kata Kunci: drama, fashion, K-Pop, Korean food, nation branding